2023
DOI: 10.3390/ijms24076755
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Next-Generation Probiotics in Obesity and Obesity-Associated Disorders: Current Knowledge and Future Perspectives

Abstract: Obesity and obesity-associated disorders pose a major public health issue worldwide. Apart from conventional weight loss drugs, next-generation probiotics (NGPs) seem to be very promising as potential preventive and therapeutic agents against obesity. Candidate NGPs such as Akkermansia muciniphila, Faecalibacterium prausnitzii, Anaerobutyricum hallii, Bacteroides uniformis, Bacteroides coprocola, Parabacteroides distasonis, Parabacteroides goldsteinii, Hafnia alvei, Odoribacter laneus and Christensenella minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 151 publications
0
31
0
2
Order By: Relevance
“…In addition, relevant studies have demonstrated that Bacteroides uniformis plays an important role in enhancing immunity levels [ 69 ]. Notably, there is also a correlation between Bacteroides uniformis and host body weight [ 70 ]. At the same time, we observed an increase in the relative abundance of Faecalibacterium prausnitzii with the DHF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, relevant studies have demonstrated that Bacteroides uniformis plays an important role in enhancing immunity levels [ 69 ]. Notably, there is also a correlation between Bacteroides uniformis and host body weight [ 70 ]. At the same time, we observed an increase in the relative abundance of Faecalibacterium prausnitzii with the DHF.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with P. distasonis has been shown to modify the Actinomycetota , Bacillota , and Bacteroidota taxa in the gut microbiota of mice [ 127 ]. Additionally, P. distasonis has been associated with improvements in adiposity, glycemia, insulin resistance, and fatty liver indices [ 128 ]. The alleviation of obesity and metabolic dysfunctions by P. distasonis has been attributed to its production of succinate and secondary bile acids [ 129 ].…”
Section: Role Of the Ngps In The Treatment And Control Of Human Diseasesmentioning
confidence: 99%
“…d’Ettorre et al [ 83 ] reported reduced morbidity and mortality in a small group of hospitalized COVID-19 patients when standard therapy was supplemented with a multi-strain probiotic formulation. This indicates the potential of investigating probiotics and NGPs regarding their safety and effectiveness as adjuvant therapy [ 84 , 85 ].…”
Section: Future Therapeutic Prospects Of Ngpsmentioning
confidence: 99%
“…The particular dose of each other NGP must also be ascertained. Also, the optimal formulation for each NGP has to be determined to enhance bacterial survival for the duration of storage and in the harsh conditions of the gut microenvironment [ 85 , 90 ]. Additionally, further studies on the concomitant administration of two or more NGPs to determine possible synergistic actions that may have beneficial additive effects.…”
Section: Future Therapeutic Prospects Of Ngpsmentioning
confidence: 99%
See 1 more Smart Citation